Introducing Perylene as a New Member to the Azaborine Family. Issue 33 (3rd July 2019) - Kaehler, Tanja; Bolte, Michael; Lerner, Hans‐Wolfram; Wagner, Matthias
Abstract: Substitutional doping of perylene with two boron atoms at the 6b/12b positions and two oxygen or nitrogen atoms at the 1/7 positions has been achieved. The modular synthesis route developed for these bis‐BO‐ (3 ) and bis‐BN‐perylenes (5 ) starts from the readily accessible borinic acid derivative of the doubly brominated 9, 10‐dihydro‐9, 10‐diboraanthracene (DBA), 1, 5‐Br2 DBA(OH)2 . A Stille‐type reaction first furnishes the alkynyl‐substituted species 1, 5‐(RCC)2 DBA(OH)2 (2 ), which undergo double ring closure to afford 3 via the gold‐catalyzed addition of the O−H bonds to the C≡C bonds. Treatment of 2 with MeN(SiMe3 )2 leads to aminoborane intermediates 1, 5‐(RCC)2 DBA(N(H)Me)2, which can be ring‐closed to give 5 in a similar manner as in the case of 3 . Different substituents R (such as Me, t BuPh) can be introduced at the 2/8 positions of the perylene core. The products obtained undergo reversible reduction and are efficient blue/turquoise emitters. Abstract : BN/CC isosterism : Doubly BO‐ and BN‐doped perylenes have been prepared, which further expand the chemical space of a ubiquitous building block for organic electronic materials. The key cyclization step proceeds via a quantitative Wacker‐type addition reaction of BO−H or BN−H bonds to adjacent alkynyl moieties.